Sensing art and artifacts: explorations in sensory museology. (2nd September 2018) - Howes, David; Clarke, Eric; Macpherson, Fiona; Best, Beverley; Cox, Rupert
ABSTRACT: This article proposes a sensory studies methodology for the interpretation of museum objects. The proposed method unfolds in two phases: virtual encounter via an on-line catalog and actual exposure in the context of a handling workshop. In addition to exploring the écart between image and object, the "Sensing Art and Artifacts" exercise articulates a framework for arriving at a multisensory, cross-cultural, interactive understanding of aesthetic value. The case studies presented here involve four objects from the collection of the Hunterian Museum as sensed and interpreted by scholars of psychology, philosophy, sociology, and anthropology. It is proposed that aesthetic judgment in the expanded (cross-cultural) sense contemplated here involves apprehending the museum object through multiple sensory modalities in place of the conventional Western fixation on visible form.